Transmissibility of Variant Influenza From Swine to Humans: A Modeling Approach - Wong, Karen K. (Clin Infect Dis, 2013)
BACKGROUND: Respiratory illness was reported among humans and swine at an agricultural fair in 2011; 3 human infections with an influenza A(H3N2) variant (H3N2v) virus were confirmed. Using epidemiologic investigation data, we sought to estimate H3N2v transmissibility from swine to humans. METHODS: We developed a model of H3N2v transmission among swine and humans and fit it to data from a cohort of 100 agricultural club members reporting swine contact to estimate transmissibility. A sensitivity analysis was performed varying H3N2v prevalence in the club cohort. Using the best-fit transmission probability, we simulated the number of swine-acquired infections among all fair attendees. RESULTS: We estimated the best-fit probability of swine-to-human H3N2v transmission per minute of swine contact. Applying this probability to 14 910 people with swine contact at the fair, we estimate that there were 80 (95% confidence interval [CI], 40–133) H3N2v infections among persons aged <20 years and 58 (95% CI, 29–96) H3N2v infections among person aged ≥20 years. CONCLUSIONS: Using early data from investigation of a new virus with unclear transmission properties, we estimated the transmissibility of H3N2v from swine to humans and the burden of H3N2v among fair attendees. Although the risk of H3N2v virus infection is small for fair attendees with minimal swine contact, large populations attend agricultural events each year, and human cases will likely occur when infected swine are present.